Pyrene terminal functionalized perylene diimide as non-fullerene acceptors for bulk heterojunction solar cells. Issue 101 (30th September 2015) - Liu, Xin; Luo, Guoping; Cai, Xinyi; Wu, Hongbin; Su, Shi-Jian; Cao, Yong
Abstract : Two perylene diimide based small molecules with different terminal groups of pyrene and tert -butyl pyrene were developed as acceptor materials in organic solar cells. Abstract : Two perylene diimide (PDI) based small molecules with different terminal groups of pyrene and tert -butyl pyrene, namelyP1 andP2, respectively, were designed and synthesized as the acceptor materials in organic solar cells (OSCs). The impacts of the different terminal groups combined with the PDI core on the optical absorption and fluorescence, electrochemical properties, film morphology, and solar cell performance were studied thoroughly. The two compounds possess a broad absorption covering the wavelength range of 400–650 nm and a relatively high LUMO energy level of 3.77 eV. Power conversion efficiency (PCE) of the OSCs based onP2 as the acceptor material andPTB7 as the donor material (1 : 1, w/w) is 0.41%. In contrast, a PCE of 1.35% was achieved for the device based onP1 as the acceptor andPTB7 as the donor (1 : 1, w/w).